Radiodocumentário "Festa dos Marujos": a alma afro-amazônica de Freguesia do Andirá (AM) - Viana, Renner Gomes (Brasil, 2024)
The present study investigates the Festa dos Marujos in Barreirinha (AM) and its relevance for maintaining and appreciating Afro-Amazonian identity. This festivity represents a cultural expression that celebrates the ethnic and cultural plurality of the Amazon region, with influences from African ancestry. Therefore, the main purpose of this research is to foster the appreciation of Afro-Amazonian identity through the Festa dos Marujos, highlighting the cultural diversity present in the celebration and encouraging intercultural interaction. With specific objectives outlined, the study aims to analyze the construction of Afro-Amazonian identity, explore popular cultural manifestations, and investigate the religious aspect underlying the festivity. To achieve these goals, a consistent methodology was adopted, combining qualitative and descriptive approaches, involving semi-structured interviews, documentary research, and direct observation. As a result of this process, a radio documentary was produced, comprehensively portraying the historical and cultural importance of the Festa dos Marujos in Freguesia do Andirá. This radio documentary not only highlighted the significant cultural meaning associated with the festivity but also emphasized the role of the radio medium in preserving local traditions. Ultimately, this study aims to broaden the reach and perpetuate traditional festive practices, promoting intercultural interaction and enhancing the cultural richness existing in the Amazon and Brazil.